(untitled) - Hayes, Nicky (London, 2003)
Covering 18 different areas of applied psychology, from the applications of knowledge to how psychologists work in the community as a whole, this new edition of Teach Yourself Applied Psychology shows readers how to apply psychology to a variety of everyday situations and contexts. It covers well-developed but unknown areas such as space psychology and eco-psychology, includes a glossary that highlights key terms, and lists further reading suggestions and relevant websites.
Keywords: Psychology, Applied; Congresses